Cellulose Acetate Based Material with Antibacterial Properties Created by Supercritical Solvent Impregnation. (4th July 2017) - Milovanovic, Stoja; Adamovic, Tijana; Aksentijevic, Ksenija; Misic, Dusan; Ivanovic, Jasna; Zizovic, Irena
Abstract : Supercritical CO2 was used as a green solvent and impregnation medium for loading cellulose acetate beads with carvacrol in order to obtain a biomaterial with antibacterial properties. Supercritical solvent impregnation was performed in a high-pressure view cell at temperature of 50°C and pressures of 10, 21, and 30 MPa with the processing time ranging from 2 to 18 h. The rate of impregnation increased with the pressure increase. However, maximum impregnation yield (round 60%) was not affected by the pressure applied. Selected samples of the impregnated cellulose acetate containing 6–60% of carvacrol were proven to have considerable antibacterial effect against Gram-positive and Gram-negative bacterial strains including methicillin-resistant Staphylococcus aureus which causes severe infections in humans and animals. In addition, cellulose acetate beads containing 6.0–33.6% of carvacrol were shown to have a porous structure with submicron pores which is of interest for the controlled delivery applications.